Motivasi Belajar Keagamaan Mahasiswa Sl Keperawatan Stikes Bina Sehat Ppni Mojokerto - Efendi, Arif (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractHumans move because of encouragement ( motivation ) from within and from outside himself . Motivation is very important in the study , since its presence is very significant in the learning process . Often in schools or faculty can be found children who art: lazy, not fun , like ditching, and so forth. This study used a descriptive design , population inthis research is one semester student a, b, and c in the prodi SI Nursing, Stikes Bina Sehat PPNI Mojokerto in 2015-20 I 6, totaled 130 students , sampling using total sampling , the total sample of 130 students , collecting data using questionnaires , and the results showed that most of the 125 ( 97,5 % ) of respondents are highly motivated , Middle motivated are that 4 ( 2 %, ) ofrespondents , while the lower motivated 1 ( 0,5 %) of respondents, counting this by using the data tabulation , High and low motivation lo learn is influenced several factors mainly instrinsic and exstrinsic factors, if one of these factors can affect the disturbed then the motivation to learn, a willingness or desire within themselves to pursue something that is to be obtained , then supported by the environment conducive , and exciting learning activities can increase the motivation to learn.Keywords: Motivation lo learn, One semester class a, b c in the prodi Sl Nursing, Learning process